(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Curculigo orchioides known as Musali or Talamuli in Ayurveda. Rhizome of C. orchioides is one of a reputed drugs mentioned in the ancient books of Ayurveda and Siddha, Unani and used as an analgesic, anti-inflammatory, spermatogenic, aphrodisiac, immunostimulant, hepatoprotective, anti-asthmatic etc. To investigate the anti-obesity activity of extract of C. orchioides root in high fat diet-induced obesity rats. The five groups in this study were, group I (normal), group II received high fat diet, group III received obese rats given orlistat (50 mg/kg, p.o.), groups IV-Obese rats given extract of C. orchioides root 500 mg/kg,p.o. and groups V-Obese rats given extract of C. orchioides 1000 mg/kg, p.o. On 30th day of experiment, blood glucoses level, lipid profile and biochemical parameter were performed. Body weight of animals was significantly (p < 0.05) maintained in all treatment groups. Progressive maintained blood glucose, lipid profile, and oxidative stress biomarkers were found in all treatment groups during study. The obtained results clearly suggested that C. orchioides possess pronounced anti-obesity potential.